Manajemen Ekstrakurikuler Muhadharah di Madrasah Aliyah - Izzati, Izzati; Fauzi, Muhammad; Isnaini, Muhammad (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This article has used a type of qualitative research with a descriptive research approach (case study) because it describes management or descriptive interpretation of the extracurricular management of muhadharah at Madrasah Aliyah Patra Mandiri Plaju Palembang. The main data sources in this study were interview data with the Head of the Madrasah, Deputy Head of Curriculum, Deputy Head of Student Affairs, teachers and Muhadharah extracurricular coaches, and 18 student representatives from each class. The findings of this study are: Planning (Planning) extracurricular muhadharah is going well as seen by involving all components responsible for the stability of activities carried out to achieve madrasa objectives, such as by holding meetings, determining classes, schedules, materials, and so on. Coaches and teachers who function as human resources for extracurricular muhadharah activities can carry out their duties properly. The implementation (actuating) of extracurricular muhadharah activities shows that madrasa leaders/representatives are less proactive in providing motivation that can generate enthusiasm at work. Supervision (controlling) extracurricular muhadharah activities at Patra Mandiri Plaju Palembang Madrasah Aliyah, this activity did not run optimally because the madrasa leadership did not formally request a written report on the activities carried out, and informally the leadership did not ask for an explanation verbally or directly on activities that have been carried out.